Bacillary angiomatosis and mycobacterium infection coexisting in a cutaneous lesion in a patient with AIDS - Chiewchanvit S. (2014)
Bacillary angiomatosis is a recently recognized bacterial infectious disease. It mainly affects patients with acquired immunodeficiency syndrome. The presence of coexistent infections of more than one pathologic process in skin lesions in patients with AIDS has been demonstrated. We report a patient with AIDS in whom both bacillary angiomatosis and mycobacterium infection were documented within the same cutaneous lesion.